Structured Palliative Care Training Enhances Nursing Competence: Evidence from Breast Cancer Care - Yanping Niu; Ling Li; Qiaozhen Xiang; Caixia Liu; Qin Lin; Pei Chen; Haipeng Song; Junhong Zhu (Palliative Medicine Reports)
Background: Advanced breast cancer patients often require palliative care (PC) to manage significant symptoms, relying heavily on nurses’ competence. Objective: Evaluate whether a structured PC training program can enhance nurses’ competence in breast cancer care. Methods: After an online announcement at Zhejiang Hospital, nurses enrolled in the PC training program. Due to the imbalance in trained and untrained nurses post-training, stratified randomization was applied, forming untrained (n = 34) and trained (n = 24) groups. The primary outcome, nursing competence, was assessed using Competency Inventory for Nursing Students at baseline and three months post-training. Subsequently, patients were recruited and assigned to different study groups based on the nurses providing their care. The untrained group (n = 167) and trained group (n = 106) received three months of inpatient PC care. European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30 and Family Caregiver Satisfaction Scale-2, as secondary outcomes, were assessed at baseline and three months post-care to evaluate the training’s impact on care quality. Results: At baseline, there were no significant differences in nursing competence or patient quality of life between the trained and untrained groups. Trained nurses showed significant improvements in general clinical skills, critical thinking, and ethics compared to untrained nurses. Patients cared for by trained nurses also demonstrated improved quality of life and higher family caregiver satisfaction. Conclusion: Structured training improves nursing competence, patient quality of life, and family caregiver satisfaction.